PROSES MORFOFONEMIK DALAM BAHASA INGGRIS DAN BAHASA SIAU (SUATU ANALISIS KONTRASTIF) - Ladi, Maryanti; Kodong, Fentje; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACT The title of this research isâ€œMorphophonemic Process of Verbs in English and Siau Language: A Contrastive Analysisâ€. The objectives of this research are to identify, analyze and describe the kinds of morphophonemic processes and finding out the similarities and the differences of morphophonemic processes in English and Siau language by using of Jensenâ€Ÿs (1990) and Ladoâ€Ÿs (1957) theories. The English data were collected from several English textbooks, such as Morphology: Word Structure in Generative Grammar (1990) by Jensen, Morphology : The Descriptive Analysis of Word by Nida (1949) and the data of Siau language were collected from books such as Morfologi Bahasa Sangir by George Bawole (1981), Habare Mapia Ko Pia Gambare by Pat Alexander (2008) and six native speakers at the age 40-71 years old in Siau. The results of this research shows that morphophonemic process are divided into ten kinds such as assimilation, dissimilation, insertion, deletion, haplology, metathesis, vocal harmony, vocal reduction, tone rules and morpheme sequence rules. Morphophonemic of verbs in English are divided into eight kinds such as assimilation, disimilations, insertion, deletion, haplology, metatesis, vocal reduction and morpheme sequence rules whereas the types of morphophonemic processes of verbs in Siau language divided into seven kinds such as assimilation, disimilations, insertion, deletion, haplology and vocal reduction and vocal harmony. The pronunciation of the morphophonemic process in both languages consists of prefixes and suffixes. The similarities that found in both languages are assimilation, disimilations, insertion, deletion and haplology, while tone rules are not found in both languages. The difference that exists in that both language are in English metathesis and morpheme sequence rules is found in English while in Siau language is not found. The reduction in English vocals occurs only as a result of the basic morpheme meeting with the affixation, whereas in Siau language occurs because of a basic morpheme meeting with prefixes and confixes.Keywords: Morphophonemic Process, English and Sangir Language, Contrastive Analysis.